Internet of Things (IoT) Based On Digital KWH Using Blynk Platform - Muhamad Taufik; Syaiful Islami; Oriza Candra; Hamdani Hamdani (Jurnal Teknik Elektro Indonesia)
Daily life cannot be separated from the use of electrical energy, such as in homes, which often cannot limit it. Accompanied by technological developments so that the internet can be used in everyday life, the concept of the Internet of Things emerged. This concept has been utilized so that it can help maximize the use of electrical energy. Using NodeMCU which has an ESP8266 Chip so it is able to connect to the internet. The Blynk platform is used for users as a tools to find out in real time the power and costs of using electrical energy. Limitations on electricity use can be set. When the electricity usage has reached the usage limit, the buzzer will turn on automatically as a warning. Another additional control that can be carried out is cutting off electricity which can be done remotely. Cutting off the electricity flow is carried out using a relay which is a switch that is operated using electricity.